Perbandingan Efisiensi Algoritma String Matchinng Knuth Morris Pratt Dan Algoritma Levenshtein Pada Aplikasi Pengarsipan Dan Pencarian Data Anggota Honda Megapro Club Indonesia - Nurul Huda; Muhammad Khafidurrohman (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
The need for data maintenance is very large, especially for data that is very important, but sometimes in searching for data there are several obstacles. Some of them were errors in writing the search text, which caused the search for data to take a lot of time and even made the data not found. Several data search methods, namely KMP and Leveshtein, have their own advantages. In this study the author aims to make a comparison between the KMP and Levenshtein methods using the Experimental research method, to find out the results of which data search method works and the search process is faster, in order to provide benefits for users to make it easier to search data. The results of the study show that the performance of the Levenshtein algorithm is superior compared to the Knuth Morris Pratt algorithm, with the result that the speed and accuracy in searching for member data is 0.022 for the average search algorithm for Knuth Morris Pratt and 0.02 for the average search algorithm. levenshtein.